Using the Fair Trade Learning Framework to Improve the Outcomes of Engagement between Universities and Off-Campus Partners: Applications and Implications for Program Design - Reynolds, Nora Pillard; MacCarty, Nordica A; Sharp, Kendra V; Hartman, Eric (Advances in engineering education, 2022)
As global engineering education projects and programs are initiated, too often social outcomes and long-term impacts are assumed to be positive. This is particularly true for sustainable development projects, which often have an inherent assumption of positive transformation through engineering solutions. We argue that a focus on technical deliverables absent prioritization of how and with whom our partnerships happen is less likely to actually lead to our desired social outcomes and longer-term impacts. We draw from the fields of community-based global learning, global development, and program evaluation to provide tools and insights for university-based engineering teams and off-campus partners to improve their long-term outcomes and impact. In particular, we draw on the fair-trade-learning (FTL) framework and core principles. We suggest adaptations to the FTL framework for engineering education, namely (i) broadening the definition of "community" to explicitly incorporate multiple types of off-campus partners, including for-profit enterprises; and (ii) more clearly distinguishing between outputs (e.g. deliverables), outcomes, and longer-term social impacts. Our analysis suggests integration of the FTL core principles of partner/community voice and direction and dual purposes increases the likelihood of achieving the desired social impact.